Patients’ preferences on atopic dermatitis skincare and social media use: a qualitative study - Roxana Mazilu; Stefanie Ziehfreund; Stephan Traidl; Alexander Zink (BMC Public Health)
Abstract Background Atopic dermatitis (AD) is a chronic inflammatory disease with a complex pathophysiology, necessitating strict therapeutic management. Over-the-counter products play a crucial role in AD treatment. The emergence of social media (SM) as a vast information source for skincare and healthy lifestyle has transformed its role from mere entertainment. This study aimed to explore the attitudes of AD patients towards SM as an information source for their AD products, understand their purchase behavior, and identify unmet needs. Methods Qualitative semi-structured interviews were conducted with AD patients recruited from a university hospital in Southern Germany and social media networks. The interviews took place between November 2022 and January 2023. The recorded interviews were transcribed verbatim and analyzed using Mayring’s qualitative content analysis. Results A total of ten patients (3 men, 7 women) aged 23–42 years were interviewed. Participants reported new perspectives in four categories: opportunities and advantages of SM as information source for AD products, risks and disadvantages, important aspects for patients’ choice of AD products, and extent and purpose of SM use in selecting AD skincare. Conclusions Patients exhibit diverse patterns of SM use when selecting daily products and critically evaluate the online content, demonstrating a greater trust in healthcare professionals or familial connections. Electronic word-of-mouth, disease severity and prior product experiences emerge as prevalent factors influencing patients’ product selection. Furthermore, female patients express interest in complementary and alternative therapies as part of an integrative therapeutical approach. Understanding patients’ needs and preferences regarding AD skincare can inform physicians in recommending more personalized therapies. Additionally, educational interventions on SM, addressing patients’ questions and concerns with evidence-based information, hold the potential for beneficial outcomes.